Requalification of the Parque dos Poderes of Campo Grande, MS: potentializing the contemporary use for the practice of outdoor physical activities - Castro, Elaíne Britto de; Rodrigues, Israel Vítor Bonfim; Casadei, Juliana de Mendonça; Machado, Flávia Cristina Albuquerque Palhares; Coutinho, Dolores Pereira Ribeiro (Revista Nacional de Gerenciamento de Cidades, 2023)
This study aimed to identify the contributions of the intervention for the requalification of the urban space of the Parque dos Poderes, a political-administrative complex in the state of Mato Grosso do Sul, in a way of encouraging the practice of outdoor physical activities and, consequentially, the improvement of quality of life of the population. The case study method was used, based on secondary data and unsystematic observations in locu. The investigated area is the Parque dos Poderes, a green area located in Campo Grande, MS, considered to be one of the tourist attractions of the city and an important leisure area for the population, which appropriated its use for the practice of outdoor physical activities, even though it was conceived for other purposes. The requalification of the Parque dos Poderes had the goal of meeting the demands of the new use of the Parque and of its users. Its design, however, favors the practice of sports such as walking, running, cycling and exercising in outdoor gyms, lacking for other audiences, such as children, elderly people, people with disabilities, and pets accompanied by their tutors.